2023
DOI: 10.1097/sla.0000000000006090
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Real-Time Patient Experience During Neoadjuvant Therapy

Alexander H Shannon,
Angela Sarna,
Luke Bressler
et al.

Abstract: Background: Neoadjuvant therapy (NT) is increasingly used for patients with localized gastrointestinal (GI) cancers. There is little data assessing patient experience and quality of life (QOL) during NT for GI cancers. Objective: To use a customized smartphone application to prospectively measure QOL and the real-time patient experience during NT. Methods: Patients with GI cancers receiving NT were instructe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…This study is part of a prospective longitudinal cohort study evaluating the patient experience during NT using a customized smartphone application. The complete protocol of this prospective study has previously been reported [ 14 , 15 ]. In brief, enrolled patients with esophageal, gastric, pancreatic, hepatobiliary, colorectal, or bladder cancer between 2020 and 2021 were instructed on how to use the application in order to document real-time symptoms and also receive monthly quality of life surveys directly through their application.…”
Section: Methodsmentioning
confidence: 99%
“…This study is part of a prospective longitudinal cohort study evaluating the patient experience during NT using a customized smartphone application. The complete protocol of this prospective study has previously been reported [ 14 , 15 ]. In brief, enrolled patients with esophageal, gastric, pancreatic, hepatobiliary, colorectal, or bladder cancer between 2020 and 2021 were instructed on how to use the application in order to document real-time symptoms and also receive monthly quality of life surveys directly through their application.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6][7] Although recent research has highlighted the significant treatment burden associated with NT, little research has focused on the patients' primary caregivers. [8][9][10] Caregivers serve an important role by providing emotional and physical support to patients throughout cancer treatment. 11 These individuals often take on the role of coordinating healthcare appointments, transporting patients to appointments, helping with activities of daily living (e.g., showering and cooking), and are the main point of contact for the wider support network of family members and friends.…”
Section: Introductionmentioning
confidence: 99%